INSTITUTIONAL DESIGN OF AN EXTERNAL OVERSIGHT BODY FOR THE CODE OF ETHICS OF CONSTITUTIONAL JUSTICES: AN INTEGRATED OVERSIGHT MODEL FROM THE PERSPECTIVE OF CHECKS AND BALANCES - Raihan Hilmy Fauzi; Arif Hidayat Hidayat (Law Research Review Quarterly, 2026)
The internal ethics oversight mechanism of the Indonesian Constitutional Court through the Honorary Council (MKMK) has proven ineffective. Dominated by active judges, it violates the nemo judex in causa sua principle, leading to structural conflicts of interest and lenient sanctions for severe ethical violations. This research aims to analyze the current existence of the Constitutional Court's ethics oversight body and formulate a new institutional design for an external oversight body based on the Integrated Oversight Model (IOM) and checks and balances perspective. This study employs a normative legal research method using statute, conceptual, and case approaches. The findings reveal that MKMK fails to meet the sociological indicators of an ideal institution, acting more as an internal protector than an objective oversight body. To resolve this, the study proposes applying the IOM, which requires returning the constitutional mandate of external oversight fully to the Judicial Commission (KY) as a unified hub. Furthermore, drawing comparative lessons from South Africa’s Judicial Service Commission, the checks and balances principle is integrated by dividing the impeachment authority: the KY acts as the investigative tribunal, while the House of Representatives (DPR) serves as the political decision-maker. In conclusion, the exclusive authority of MKMK must be revoked. Establishing a permanent ethics council under the KY, without active constitutional judges, is highly recommended to guarantee true independence and public accountability.